Corn shoot and grain nutrient uptake affected by silicon application combined with Azospirillum brasilense inoculation and nitrogen rates - Galindo, Fernando Shintate [UNESP]; Pagliari, Paulo Humberto; Buzetti, Salatiér [UNESP]; Rodrigues, Willian Lima [UNESP]; Fernandes, Guilherme Carlos [UNESP]; Biagini, Antônio Leonardo Campos [UNESP]; Marega, Evelyn Maria Rocha [UNESP]; Tavanti, Renan Francisco Rimoldi [UNESP]; Jalal, Arshad [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP] (Taylor & Francis, 2021)
This study was developed to investigate if Ca and Mg silicate application as Si source combined with inoculation with Azospirillum brasilense and N rates can affect corn nutrient uptake. The study was set up in a Rhodic Hapludox under no-till system, located in Selvíria, state of Mato Grosso do Sul, Brazil. Treatments included: (i) two seed inoculation (with and without A. brasilense); (ii) two soil amendment sources (Ca and Mg silicate as Si source and dolomitic limestone); and (iii) five N application rates applied as side-dress (0 to 200 kg ha−1). Increasing N rates positively influenced corn nutrition with increased nutrient and Si uptake in shoot and grain. The average nutrient uptake in descending order was K > N > Ca > Si > Mg > S > P >Fe > Mn > Zn > Cu > B for shoot and N > K > P > S > Mg > Ca > Si> Fe > Zn > Mn > B > Cu for grain. Calcium and Mg silicate application positively influenced corn nutrition with greater shoot P, K, Ca, S, and B uptake and grain Ca uptake. Inoculation with A. brasilense was found to increase nutrient uptake with greater shoot N, K, Ca, B, and Si and grain Cu uptake. Grain N and S increased by 22.5 and 26.8% when plants were inoculated and 200 kg N ha−1 was applied and grain Zn increased by 88.6, 65.7, and 99% when plants were inoculated and 50, 150, and 200 kg N ha−1 were applied, respectively. Therefore, studies conducted under tropical conditions are needed to better understand the role of Si combined with PGPB inoculation under different N management and their effects on plant nutrition and cereal development aiming at improving nutrient replenishment.
Keywords: nitrogen management; nutrient accumulation; plant growth promoting bacteria; silicon in agriculture; Zea mays L